The peculiarities of multiple sclerosis clinical course in the South of Russia (on the example of Rostov Region) - Z. A. Goncharova (Бюллетень сибирской медицины)
In order to improve multiple sclerosis (MS) diagnosing and specify the influence of climatic and geographic factors on the clinical picture of the disease, the peculiarities of its course and clinical polymorphism in the population of Rostov region were studied. The analysis was conducted to compare the main characteristics of MS in Rostov Region (prevalence — 27,2 : 100 000 of its population) and the area with a considerably bigger rate (Novosibirsk — 54,36 : 100 000). The distinctive peculiarities of the disease among people living in the South of Russia (on the example of Rostov Region) are slow progression and wide clinical polymorphism.